The Magnetosphere as a Complex System - Stepanova, M (2013)
The magnetosphere is a multi-scale spatio-temporal complex dynamical system. In this context, we have analyzed the multifractal behavior of the AL index, as a proxy for an energy dissipation rate, using discrete wavelet leaders. This technique allows the calculation of the spectrum for both positive and negative values of q, giving a robust peak at h?0.5. The same technique is applied to the dissipation rate of a simple 1D model of intermittent magnetic field annihilation, showing a clear multifractal behavior, but with a peak at h?0.2. Even though this intuitive 1D model, because of its simplicity, is not expected to reproduce all the complex dynamics that occur in the Earth s magnetotail, it suggests that the existence of a multifractal dissipation dynamics is necessary to the establishment of the self-organized state, as shown in a 2D simulation of intermittent plasma dynamics.© 2012 COSPAR. Published by Elsevier Ltd. All rights reserved.